cos(x + 45) + cos(x - 45) = sq. root 2 cosx !?
cos(x+45) = cosxcos45 - sinx sin45 = 5sqrt(2)(cosx -sinx)
cos (x-45) = cosxcos45+ sin x sin45=.5sqrt(2)(cos x+sinx)
So cos(x+45) +cos(x-45)= sqrt(2)(cos x)
sqrt(2)(cos x) = sqrt(2)cos x
2007-01-08 14:50:06
·
answer #1
·
answered by ironduke8159 7
·
0⤊
0⤋
Equations involving a "variable" have this nasty habit of having x's.
Sin, cos... are functions (they are trigonometric functions) and, like any functions, they can be applied to a variable, just like powers, square roots and logarithms.
Using letters to replace numbers is a mathematician's way to see how an equation behaves for all values (at least, all values that one would allow for x).
You can use the x the same way you can use a number.
For example, there exists an identity:
cos(a+b) = cos(a)*cos(b) - sin(a)*sin(b)
It does not matter what values you use for a and b, the equation remains true.
So, we will use x and 45 instead of a and b.
cos(x+45)= cos(x)*cos(45) - sin(x)*sin(45)
it just so happens that cos(45) = sin (45) = 1/sqrt(2)
Next, use x and -45 for a and b
cos (x-45) = cos(x)*cos(-45) - sin(x)*sin(-45)
here, we have cos(-45) = cos(45) = 1/sqrt(2)
and sin(-45) = - sin(45) = -1/sqrt(2)
So far, we have:
cos(45+x) + cos(45-x) =
cos(x)*cos(45) - sin(x)*sin(45) + cos(x)*cos(-45) - sin(x)*sin(-45) =
cos(x)*( cos(45)+cos(-45) ) + sin(x)*( -sin(45) - (-sin(45)) ) =
cos(x)*(1/sqrt(2) + 1/sqrt(2)) + sin(x)*(-1/sqrt(2) + 1/sqrt(2))
The sin(x) disappear because it is multiplied by 0
You are left with cos(x)*(2/sqrt(2))
you can show that 2/sqrt(2) = sqrt(2) and you are done.
2007-01-08 14:47:14
·
answer #2
·
answered by Raymond 7
·
0⤊
0⤋
Cos(x+45) = Cos(x)Cos(45)+Sin(x)Sin(45)
Cos(x-45) = Cos(x)Cos(-45)+Sin(x)Sin(-45)
Sin parts cancel out since sin(45) = - sin(-45).
so 2 Cos(x)^2 (SQRT(2)/2)^2 = SQRT(2) Cos(x) - almost there
2 Cos(x)^2 = SQRT(2) Cos(x)
Cos(x) = SQRT(2)/2
Well, you can solve from there.x=45
Check
Cos(45+45)+Cos(45-45)=SQRT(2)Cos(45)
1 + 0 = SQRT(2) x SQRT(2)/2 = 1 - checked
2007-01-08 15:03:41
·
answer #3
·
answered by Dr Dave P 7
·
1⤊
0⤋
I prefer radians; it's all the same though. 45 degrees = pi/4
cos(x + pi/4) + cos(x - pi/4) = sqrt(2) cos(x)
Choose the left hand side (LHS) since it's the more complex side.
Remember the cos addition identity:
cos(a + b) = cos(a)cos(b) - sin(a)sin(b)
cos(a - b) = cos(a)cos(b) + sin(a)sin(b),
and apply it here.
LHS = cos(x + pi/4) + cos(x - pi/4)
LHS = cos(x)cos(pi/4) - sin(x)sin(pi/4) + cos(x)cos(pi/4) +
sin(x)sin(pi/4)
Note that we see immediately that the terms containing the sines will cancel each other out (one is plus, one is minus).
LHS = cos(x)cos(pi/4) + cos(x)cos(pi/4)
Being two exact things, we combine them into one.
LHS = 2cos(x)cos(pi/4)
cos(pi/4) = sqrt(2)/2, so
LHS = 2cos(x) [sqrt(2)/2]
The 2 will cancel out.
LHS = cos(x)sqrt(2)
Multiplication is commutative, so
LHS = sqrt(2)cos(x) = RHS
2007-01-08 14:39:19
·
answer #4
·
answered by Puggy 7
·
2⤊
0⤋